2014
DOI: 10.1038/srep07514
|View full text |Cite
|
Sign up to set email alerts
|

Modulation properties of factors released by bone marrow stromal cells on activated microglia: an in vitro study

Abstract: In the present paper we develop a new non-cell based (cell-free) therapeutic approach applied to BV2 microglial cells and spinal cord derived primary microglia (PM) using conditioned media from rat bone marrow stromal cells (BMSCs-CM). First we collected conditioned media (CM) from either naive or injured rat spinal cord tissue (SCI-CM, inflammatory stimulation agent) and from rat bone marrow stromal cells (BMSCs-CM, therapeutic immunomodulation agent). They were both subsequently checked for the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 73 publications
6
28
0
Order By: Relevance
“…In addition, we also recorded during LPS activation BV2 cells elongated and extended from the mostly short and compact morphology to a long shape. This finding coincides with a previous report in which BV2 cells were incubated in the conditioned medium from spinal cord injury for 3–48 h [49]. We provided quantitative descriptions for changes in morphology as decreased cell circularity with increased Feret’s diameter and confirmed that the changes ultimately led to the augmented cell area and perimeter.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we also recorded during LPS activation BV2 cells elongated and extended from the mostly short and compact morphology to a long shape. This finding coincides with a previous report in which BV2 cells were incubated in the conditioned medium from spinal cord injury for 3–48 h [49]. We provided quantitative descriptions for changes in morphology as decreased cell circularity with increased Feret’s diameter and confirmed that the changes ultimately led to the augmented cell area and perimeter.…”
Section: Discussionsupporting
confidence: 91%
“…Some other factors not related to MSC so far but that were recently shown to have regenerative and neurotrophic functions are the ASC-secreted Macrophage-colony stimulating factor (MCSF), Matrix metalloproteases (MMPS), Follistatin (FST)-like 1, Mesencephalic astrocyte-derived neurotrophic factor (MANF), and Neuron derived neurotrophic factor (NDNF) [38]. Others like Semaphorins (SEM), Galectins (Gal), Platelet-derived growth factor (PDGF) and Transforming growth factor-beta (TGF-b) were found in the secretome of BMSCs by Cizkova et al [39]. Altogether, these results suggest the existence of tissue-source based differences, as recently evidenced by Pires et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs at a density of 3 × 10 5 cells were used for the phenotypic analysis using flow cytometry [26]. In brief, the cells were stained with phycoerythrin-(PE-) labeled primary antibodies against CD11, CD73, and the corresponding isotype control antibody of rat IgG1, in the dark at room temperature, and then fixed in 1% paraformaldehyde (PFA), after being washed twice with ice-cold PBS.…”
Section: Immunophenotypical Analysis Of Bmscsmentioning
confidence: 99%